(untitled) (Vietnam Journal of Community Medicine, 2025)
In the Mekong Delta, fish is a popular food, especially fish with small, hard bones, and people have a habit of eating quickly. Hence, they are the most common foreign objects in the oropharyngeal cavity among most patients. A 67-year-old male patient presented to our clinic with a painful swelling in the submandibular gland region that had persisted for five weeks. He did not recall any previous history of foreign objects entering the area, either through the oral cavity or the skin. The patient reported that the swelling had decreased in size after receiving treatment at a local hospital, but it did not fully resolve. By using the echography and CT scan, we determined the foreign body in the submandibular gland (suspecting a fish bone). So the patient was undergoing an operation to remove the foreign body, after the surgery, we removed one fish bone (about 15-16mm in length). This is a sporadic case of a fish bone in the submandibular gland without the penetrating site at the oropharyngeal cavity or skin. Therefore, in a patient with swelling of the gland like this, one should undergo imaging tests to determine the cause and establish a correct treatment.